Yersinia enterocolitica Prosthetic Joint Septic Arthritis Successfully Treated with Ceftriaxone - Hafez M. Abdullah; Mansi Oberoi; Abdelmohaymin Abdalla; Smitha Narayana Gowda; Moataz Ellithi (Case Reports in Infectious Diseases)
Yersinia enterocolitica is a Gram-negative coccobacillus that is known to cause gastroenteritis and symptoms mimicking appendicitis or terminal ileitis. It is also one of the culprit infections implicated in causing reactive arthritis. Rarely, it can cause musculoskeletal infections including osteomyelitis, septic arthritis, and discitis. We describe the case of a 70-year-old female with multiple comorbidities who presented with left knee pain and swelling after recent gastroenteritis. She was found to have Yersinia enterocolitica septic arthritis in her left knee prosthetic joint. The patient underwent an exchange of her prosthetic material and was successfully treated with a six-week course of ceftriaxone. Our article aims to highlight a rare manifestation of Yersinia enterocolitica infection and to point out an important differential for reactive arthritis after Yersinia enterocolitica infection.